Literatura ou a arte de contar a História: bibliografia alusiva às Campanhas Peninsulares - Margarida Reffóios (Carnets)
With this paper, we firstly aim to present an account of some texts written by French authors /protagonists during the French Invasions, such as Laure Permont (Duchess of Abrantes) or Jacome Ratton. Secondly we will endeavour to mention some of the many Portuguese writings which date back to that period. By referring to opposed ideologies, we can affirm that the bibliography which concerns the Peninsular Campaigns is dense and leads us to two dimensions of fertile observation: the so-called scientific literature and the historical novel. Finally we will attempt at analysing the new bibliography which was ‘reborn’ with the commemoration (second centenary) of the French presence in Portugal, quoting authors such as Graça Moura or Luz Soriano.